Labor Absorption, Inflation Volatility, and Inflation Targeting Framework (ITF): The Case of Three Economic Sectors in Indonesia - Meilianna, Ruth (Journal of Indonesian Social Sciences and Humanities, 2020)
Labor is one of the important inputs affecting shocks in economy. Various economic problems increase when unemployment is high. High volatility (uncertainty) at prices (this study used inflation), is a risk for the company. When facing the uncertainty, the company can choose to delay investing and change the decisions in recruitment plan; it is used to collect the information about prices before investing (this concept called Irreversible Investment), subsequently cause a reduction in labor absorption. Moreover, this uncertainty is a cost for the company. This condition makes it difficult for companies to determine the optimal number and combination of inputs (including labor), as consequences the company has to decide reducing the inputs. Inflation Targeting Framework (ITF) is one of the frameworks used by Bank Indonesia and the government to reduce and stabilize inflation. There are pros and cons of the irreversible investment concept and the success of the ITF. This study aims to determine whether uncertainty in inflation (illustrated by inflation volatility) affects investment and labor absorption. In addition, it is to find out whether the ITF has succeeded in making inflation stable and affecting other macroeconomic variables. The data used are annual data from volatility of inflation, employment, investment, GDP and ITF dummy. This study used three sectors in Indonesia, for instance, the industrial; trade, restaurants, accommodation services and transportation sector; and transportation, warehousing and communication, because of limited data. The result of this study was that volatility affect the labor absorption, both directly and indirectly (through investment). Furthermore, the ITF has affected the volatility of inflation.